The Implementation of Brainstorming Method as Effort to Improve Motivation and Study Result of Students on Linear Program Course in Mathematics Education of Riau University - Anggaini, Rini Dian; Murni, Atma (Proceedings of the UR International Conference on Educational Sciences, 2018)
The kind of this research is a Classroon Action Research. The purpose of this research is to increase the motivation and study result of students in Mathematics Education study program FKIP UNRI who follow the Linear Program course by applying the Implementation of Brainstorming method. Learning is carried out by applying the implementation of the Brainstorming method through five stages: (1) providing information and motivation (orientation); (2) identification (analysis); (3) classification (synthesis); (4) verification and (5) conclusion (agreement). The subject of this research 40 students which follow was conducted in two cycles, from cycle I to cycle II. The results show that there was an increase of studentsâlearning motivation almost in all indicators. The percentage of students who scored âvery goodâ, increasing from 10% to 20% and the percentage of students who scored âgoodâ, increasing from 20% to 27.5%. The percentage of students who scored âgood enoughâ and âdeficientâ decreased respectively from 32.5% to 25% and from 27.5% to 17.5%. While the percentage of students who scored âvery deficientâ is permanent.